Micro-Refractometry and Local-Field Mapping with Single Molecules - Naumov, A. V; Gorshelev, A. A; Gladush, M. G; Anikushina, T. A; Golovanova, A. V; Köhler, J; Kador, L (Nano letters, 2018)
The refractive index n is one of the most important materials parameters of solids and, in recent years, has become the subject of significant interdisciplinary interest, especially in nanostructures and meta-materials. It is, in principle, a macroscopic quantity, so its meaning on a length scale of a few nanometers, i.e., well below the wavelength of light, is not clear a priori and is related to methods of its measurement on this length scale. Here we introduce a novel experimental approach for mapping the effective local value n ∼ of the refractive index in solid films and the analysis of related local-field enhancement effects. The approach is based on the imaging and spectroscopy of single chromophore molecules at cryogenic temperatures. Since the fluorescence lifetime T 1 of dye molecules in a transparent matrix depends on the refractive index due to the local density of the electromagnetic field (i.e., of the photon states), one can obtain the local n ∼ values in the surroundings of individual chromophores simply by measuring their T 1 times. Spatial mapping of the local n ∼ values is accomplished by localizing the corresponding chromophores with nanometer accuracy. We demonstrate this approach for a polycrystalline n-hexadecane film doped with terrylene. Unexpectedly large fluctuations of local-field effects and effective n ∼ values (the latter between 1.1 and 1.9) were found.